Kinetic Aspects of the Interaction of Blood Clotting Enzymes - Hemker, H. C; Muller, A. D (Thrombosis and Haemostasis, 1968)
Observations of the clotting time in one-stage tests in the extrinsic system show, after suitable correction, that there is a rectilinear relationship between the clotting time and the inverse of the concentration of the rate-limiting factor. This cannot be explained by the “cascade” or “waterfall” mechanism proposed as a scheme for the interaction of the blood-clotting factors concerned. This relationship can, however, be explained by a slightly different mechanism.